Dimensional Analysis of Spatial Inequality in Regional Development: Evidence from the Noun Division, West Region of Cameroon - Tafuh, Desmond Forbah; Kometa, Sunday Shende; Kimengsi, Jude Ndzifon (Environmental Management and Sustainable Development, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Spatial inequalities in regional development continue to exist on a global, regional, national, and local scale. The nature and magnitude of spatial inequality in regional development seems not to have been clarified in the Noun Division even though much interest appears to be given only to income inequality despite the fact that spatial inequality in socio-economic development seemingly exist. This paper provides empirical evidence on the dimensions of spatial inequality in regional development in the Noun Division. The situation is examine using simple random sampling technique to select 400 household representatives with the used of questionnaires as the main instrument for data collection. Data collected were analysis using descriptive and inferential statistics in Microsoft Excel 2016 and SPPS<sub style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">21<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">. Dimensional analysis confirms that there exists spatial inequality in regional development with Foumban and Foumbot Sub Divisions rapidly developing in the Noun Division. The study concluded that there exist spatial inequality in regional development between Sub Divisions in the Noun. Based on this finding, it is recommended that the way forward to balance the imbalance between Sub Divisions is to target investments in lagging Sub Divisions taking into consideration variation the distribution of socio-economic development in the Noun Division.